Awareness regarding safe abortion among undergraduate students - Kumari Gupta Teli, Pooja; Thapa, Taniya; Sharma, Sabita (Journal of Chitwan Medical College, 2024)
Background: Abortion is safe when they are carried out with a method that is recommended by (WHO, World Health Organization) and that is appropriate to the pregnancy duration, and when the person carrying out the abortion has the necessary skills. The aim of the study was to assess the level of awareness regarding safe abortion among undergraduate students at Bharatpur, Chitwan. Method: A descriptive cross-sectional study was conducted at Bharatpur Hospital, Chitwan, from February to July 2023. Convenience sampling technique was used among the people who met the inclusion criteria. Ethical approval was obtained. The data were analyzed for knowledge, preventive practices, and socio-demographic association. The SPSS version 20 was used for descriptive as well as inferential statistics. A p-value < 0.05 was considered statistically significant. Result: Out of 130 respondents, more than half 59.2% were adequately aware about of safe abortion whereas 40.8% were inadequately aware about of safe abortion. Statistically, there was a significant association between types of family and level of awareness (p=0.002) Conclusion: More than half of the undergraduate students in this study had adequate awareness of safe abortion, but around half had limited knowledge about the timing, particularly that it is safe up to 12 weeks of gestation. An awareness program could improve understanding of all aspects of safe abortion.